Liquid-Cooled Thermoelectric Modules: Potential for Efficient Water Harvesting Through Air Condensation - Prasetyo, Bowo Yuli; Yuliane, Aindri; Rosulindo, Parisya Premiera; Wang, Fujen (Makara Journal of Technology, 2024)
Water is one of the essential natural resources for the sustaining life of all beings on this planet. In general, groundwater is used to meet daily needs, although the availability of this water source becomes a major concern, particularly in some areas with limited access to it. Air condensation is a solution for providing water in such areas. This study aims to explore the potential of utilizing the thermoelectric technology as an alternative solution for water provision. An experiment is conducted using a system consisting of single liquid-cooled thermoelectric cooling devices/modules (TECs). Three types/variants of TECs with different cooling capacities are tested at three different operating voltages. During the tests, changes in physical quantities are recorded for analysis, along with amount of water produced. The results demonstrate notable performance differences between all TEC variants. The highest cooling capacity is achieved by the TEC-1 variant, albeit with higher current usage. The TEC-3 variant delivers the lowest performance of all. TEC-2 obtains the highest water yield, producing 46.9 g of water at 12 V, while TEC-1 and TEC-3 produce 34.4 and 13.2 g, respectively. The highest condensation rate, i.e., 3.72%, is achieved by TEC-2, at 9 V, while the lowest energy consumption, i.e., 3.74 kWh/L, is shown by TEC-2, at 12 V.